2003
DOI: 10.1007/s00421-003-0835-1
|View full text |Cite
|
Sign up to set email alerts
|

Mechanomyographic responses during voluntary ramp contractions of the human first dorsal interosseous muscle

Abstract: The aim of this study was to examine the mechanomyogram (MMG) and force relationship of the first dorsal interosseous (FDI) muscle as well as the biceps brachii (BB) muscle during voluntary isometric ramp contractions, and to elucidate the MMG responses resulting from the intrinsic motor unit (MU) activation strategy of FDI muscle with reference to the MMG of BB muscle. The subjects were asked to exert ramp contractions of FDI and BB muscle from 5% to 70% of the maximal voluntary contraction (MVC) at a constan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
113
1
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(121 citation statements)
references
References 37 publications
5
113
1
2
Order By: Relevance
“…The facts presented can be attributed to the increase in mechanical activity resulting from the sum of the action potentials (APs) of the MUs with the increase of muscular force (Yoshitake et al, 2002) even in lower magnitudes (Akataki et al, 2003). This process occurs because of the redistribution of aqueous material present in the sarcoplasm (Neering et al, 1991), and because the mechanical signals generated from this process travel through the material between the muscle and the sensor (Dalton and Stokes, 1993).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The facts presented can be attributed to the increase in mechanical activity resulting from the sum of the action potentials (APs) of the MUs with the increase of muscular force (Yoshitake et al, 2002) even in lower magnitudes (Akataki et al, 2003). This process occurs because of the redistribution of aqueous material present in the sarcoplasm (Neering et al, 1991), and because the mechanical signals generated from this process travel through the material between the muscle and the sensor (Dalton and Stokes, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…The use of MMG as indicator of the level of MUs firing rates, as well as indicator of increase of the action potentials (APs) originated from the skeletal muscle (Akataki et al, 2003), may be subject to attenuation in acquisition caused by thicker layers of subcutaneous fat. Therefore, it is important to consider the effects of fat when adopting MMG as a tool in applications such as prostheses control (Orizio et al, 2003), monitoring of muscular fatigue (Orizio et al, 2003;Scheeren et al, 2010;Tarata, 2003), neuromuscular diseases diagnosis (Hu et al, 2007), respiratory muscle work (Sarlabous et al, 2014), among others.…”
Section: Discussionmentioning
confidence: 99%
“…For the biceps brachii, several recent studies have reported increases in both MMG amplitude and MMG mean power frequency with submaximal isometric torque (Akataki, Mita, Watakabe, & Itoh, 2001;Akataki et al, 2003;Beck et al, 2004;Orizio et al, 1989;. At torque levels ≥ 60-80% MVC, however, MMG amplitude for the biceps brachii plateaus or decreases (Akataki et al, 2001;Beck et al, 2004;Orizio et al, 1989;.…”
mentioning
confidence: 99%
“…During voluntary contractions, the asynchronous motor unit activities are summated to form the surface MMG, and it has been suggested that the time and frequency domains of the MMG signal may provide information regarding the unique motor unit activation strategies (motor unit recruitment and firing rate) that modulate isometric torque production in various muscles (Akataki, Mita, Watakabe, & Itoh, 2003;Orizio, 1993;Orizio et al, 2003;Orizio, Liberati, Locatelli, De Grandis, & Veicsteinas, 1996;Orizio, Perini, Diemont, Figini, & Veicsteinas, 1990;Orizio, Perini, & Veicsteinas, 1989). Specifically, it has been shown that MMG amplitude is related to motor unit recruitment, while the frequency domain of the MMG signal may contain information about motor unit firing rate (Akataki et al, 2003;Orizio, 1993;Orizio et al, 2003;Orizio, Solomonow, Baratta, & Veicsteinas, 1993).…”
mentioning
confidence: 99%
See 1 more Smart Citation